2007
DOI: 10.1007/s00436-007-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Habitats of Bulinus truncatus and Planorbarius metidjensis, the intermediate hosts of urinary schistosomosis, under a semiarid or an arid climate

Abstract: Since Bulinus truncatus and Planorbarius metidjensis are the intermediate hosts of Schistosoma haematobium in southwestern Morocco, five rivers were investigated to identify sites colonized by either of both species and determine the characteristics of their habitats via the study of 12 physicochemical parameters in running water. P. metidjensis was observed in the upper valleys of three rivers, whereas B. truncatus was found in sites of lower altitude. A component analysis demonstrated that altitude (from 4 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
4
0
4
Order By: Relevance
“…2). These conditions are very similar to those populations studied by Yacoubi et al (2007). Known distribution (Fig.…”
Section: Introductionsupporting
confidence: 84%
“…2). These conditions are very similar to those populations studied by Yacoubi et al (2007). Known distribution (Fig.…”
Section: Introductionsupporting
confidence: 84%
“…The molluscan intermediate host in this region is Planorbarius metidjensis . In general, this snail aestivates in the muddy banks of dried up water-courses during the hot summer months, interrupting the parasite's life cycle (Ramjo-Martin and Simon-Vincente, 1988; Yacoubi et al 2007). Consequently, a transmission window exists only during the autumn and spring months when temperatures are cooler and thus S. bovis cercariae would appear to demonstrate thermostability at temperatures that most closely reflect climatic conditions during these seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ammonium, nitrite and chloride ions were found at variable concentrations in all types of water In addition according to the manufacturer, calcium, bicarbonate and sulfate ions were present in the commercial mineral water with a relatively low conductivity compared to well water and ground pump water. These essential mineral compounds also found in snail breeding sites may have different impact on their development and abundance depending on snail species ( Bakhoum et al., 2019 ; Yacoubi et al., 2007 ). Their absence or low level concentration in distilled water could explain the high and earlier mortality of B. pfeifferi and B. senegalensis observed in the distilled water, unlike what is observed with B. truncatus .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the delta of the SRB, the population density of this species is higher in areas with lower salinity ( Bakhoum et al., 2019 ). On the other hand, such laboratory research could help to better understand snail population dynamics and preferred habitat, predict their behavior to global environmental change ( Yacoubi et al., 2007 ) and develop control measures such as those attempting to control cercariae through water chlorination ( Braun et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%